β dependence of the Witten index - Alves, N. A.; Aratyn, H.; Zimerman, A. H. (Elsevier, 1986)
The ß-dependence of the regularized Witten index is commented on in supersymmetric quantum mechanics focusing on the problem of periodic boundary conditions and the normalization of the corresponding eigenstates. © 1986.